Avoiding the Next Financial Crisis - Farizan Tarudin (Asian Journal of Political Economy, 2019)
"Over-the-counter derivative contracts bind institutions together in a network of opaque, credit risks the size and characteristics of which can change rapidly and can be said to be not understood with a high degree of precision, including by market participants themselves." (Garry J. Schinasi, 2006). In the light of the subprime crisis, this analysis of one of the financial experts of the International Monetary Fund (IMF) appears particularly premonitory. Throughout his book analyzing financial instability, Schinasi argues that the developments in contemporary finance have resulted in a decline in transparency of transactions and opacification of how to take risks, both at home and abroad, the eyes of public actors only in the eyes of private actors. Now that the empirical demonstration of this general principle is made, what are the proposed answers to try to remedy it? Four major solutions seem to be distinguishable. The first favors reflection on the content of monetary policy. The other three recognize a purely financial dimension to recent slippages and propose regulatory interventions of different intensities.
Keywords: G01; 330; Financial Crises